Deep seated fault‐related volcanogenic H2S as the key agent of high sinkhole concentration areas. Issue 3 (9th November 2018) - Santo, A.; Santangelo, N.; Balassone, G.; Strauss, H.
Abstract: Karst collapse sinkholes (KCS) are a peculiar karst morphology resulting from the collapse of the topographic surface caused by subsurface karstification. In the Southern Apennines these phenomena are not randomly distributed but concentrate in several zones, named High Sinkhole Concentration Areas (HSCA), showing peculiar geological, structural and hydrogeological conditions. Gas vents and mineral springs occur widely in these HSCA, and are often stricty related to the KCS. Starting from four representative areas, the aim of this study is to ascertain if there is a genetic link between peculiar mineralogical vs geochemical features of densely fractured/altered rocky masses in KCS, gas vents/springs occurrences and diffuse hypogenic karstification. By means of a multidisciplinary approach (geological/geomorphological, mineralogical and geochemical) we selected and analysed four different kinds of samples related to KCS, gas vent and spring occurrences: (i) altered to deeply altered limestones sampled in the sinkholes; (ii) unaltered limestones sampled in close proximity to sinkhole areas; (iii) gypsum‐rich crusts/patinae, precipitated near to gas vents; (iv) gypsum‐ and calcite‐rich precipitates occurring at springs or inside caves. Among neoformed non‐carbonate minerals, gypsum is virtually ubiquitous, halides (fluorite, halite, sylvite) also occur in small to trace amounts. The mineralogical assemblages of the different samples show similarities and may also be compatible with hypogenic speleogenesis and with a process of alteration of the carbonate bedrock by means of uprising mineralizing fluids along structural discontinuities. Stable isotopic compositions (S, O) display strong variability in δ 34 S and δ 18 O for sulfate in the different areas, but a deep‐seated sulfur source can be hypothesized for many of the studied KCS‐related samples. This study has important implications for the relationships between areas of high concentration of sinkholes, regional fault systems, mechanical characteristics of rocks and the high seismicity typical of these areas of the Southern Apennines. © 2018 John Wiley & Sons, Ltd. Abstract : This study focuses on areas whit high concentration of karst collapse sinkholes. Here sinkholes occur along damage zones and mineral/thermal springs and/or gas vents are always present in the vicinity. Peculiar mineral associations together geochemical data testify that the rock alteration can be explained by the activity of volcanogenic H2 S uprising along faults, causing hypogene karst processes.